﻿More hidden diversity in a cryptic species complex: a new subspecies of Leptideasinapis (Lepidoptera, Pieridae) from Northern Iran - Nazari, Vazrick; Lukhtanov, Vladimir A; Naderi, Alireza; Fric, Zdenek Faltýnek; Dincă, Vlad; Vila, Roger (Comparative cytogenetics, 2023)
A new subspecies of Leptideasinapis from Northern Iran, discovered by means of DNA barcoding, is described as Leptideasinapistabarestanassp. nov. The new subspecies is allopatric with respect to other populations of L.sinapis and is genetically distinct, appearing as a well-supported sister clade to all other populations in COI-based phylogenetic reconstructions. Details on karyotype, genitalia, ecology and behaviour for the new subspecies are given and a biogeographical speciation scenario is proposed.
Keywords: taxonomy; allopatry; butterflies; Wood White; Palearctic; DNA barcoding